Multifunctional bionanocomposites with ultraviolet blocking, infrared reflection and thermal conductivity - Decol M.* (2020)
© 2020 Society of Plastics EngineersThe objective of this paper is investigating the effect of different localizations of titanium dioxide (TiO2) and hexagonal boron nitride (hBN) nanoparticles in the poly(lactic acid) (PLA)/poly(ε-caprolactone) (PCL) blends on the ultraviolet (UV) blocking, infrared reflection (NIR), and thermal conductivity of the nanocomposites for the fabrication of bionanocomposites with high performance. Transmission electron microscopy images demonstrated that the different mixing sequences induced different nanoparticle localization in the immiscible PCL/PLA blend. These different localizations yielded differences in the properties of the hybrid quaternary nanocomposite. When the nanoparticles had different localizations, TiO2 at the interface and hBN in the PCL phase, the thermal conductivity was 0.86 Wm−1 K−1, 100% of UV radiation (λ = 300 nm) was blocked and 74% of NIR radiation was reflected. This nanocomposite has a strong potential for application as a multifunctional biodegradable film for agriculture, capable of absorbing UV radiation, reflecting NIR radiation, and conducting thermal energy.